Teaching and Learning Keyboarding: - Byers, Emily (My University, 2004)
The purpose of the research was to compare the effects of covered keyboarding instruction with uncovered keyboarding instruction on students' typing proficiency and typing technique. The instruction occurred over a six-week period in two seventh grade beginning keyboarding classes. Forty-four students participated in the instruction.
Keywords: Covered Keyboarding; Uncovered Keyboarding; Student Typing